Implementation of Degenerative Diseases and Stunting Prevention Program in Kradenan Utara Hamlet, Magelang Distric - Wahyuningtyas, Eka Sakti; Nugroho, Sri Hananto Ponco; Wijayatri, Ratna; Sabrien, Diva Adela; Azzahra, Ni'matun Nada; Khasanan, Putri Uswatun; Aisyah, Shofi Afra; Aulia, Salshabilla Ramadhisa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This PPMT (Pengabdian Pada Masyarakat Terpadu) activity is related to prevention and management programs for degenerative diseases and stunting to improve community welfare holistically, especially in Kradenan Utara Hamlet. The types of degenerative diseases include hypertension, Diabetes Mellitus, and gout or uric acid. Therefore, to anticipate the existence of these diseases, disease screening is carried out through screening examinations for degenerative diseases for the community, giving herbal medicine for the management of degenerative diseases, education on stunting problems, and workshops on making tea from Salak as management of degenerative diseases. This PPMT implementation aims to empower the community related to preventive programs in degenerative diseases and stunting to improve holistic public health in North Kradenan Hamlet, Kradenan Village, Srumbung District, Magelang Regency. The method used in this community service is through educational, participatory, and community development methods. This PPMT (Pengabdian Pada Masyarakat Terpadu) activity has a beneficial impact on the community in Kradenan Utara Hamlet being able to understand how to prevent stunting, which initially did not know to understand better. The community knows the risk of degenerative diseases. The result of this PPMT is the follow-up of several work programs to monitor degenerative diseases and their treatment using herbs (medicinal plants), namely herbal medicine and Salak tea, and monitoring stunting problems.